Feasibility of salvage selective neck dissection after primary irradiation of pharyngeal and laryngeal carcinoma - Mat Lazim, Norhafiza Hanis Izzuddin; Abdullah, Kahairi; Karakullukçu, Barış M.; Tan, Ing Bing (Karger, 2018)
Introduction: The concept of neck dissection (ND) in the management armamentarium of head and neck squamous cell carcinoma has evolved throughout the years. Nowadays, ND becomes more functional. Methodology: A retrospective study of 865 patients was performed at Netherlands Cancer Institute-Antoni Van Leeuwenhoek Hospital to investigate the feasibility of selective ND (SND). All patients with squamous cell carcinoma of the pharynx and larynx who received primary radiation and underwent salvage ND were included in the study. Result: A total of 29 NDs were analyzed. In 17 neck sides, viable metastases were found (58%), whereas in the other 12 specimens there were no viable metastases. In 16 of the 17 necks (94%), the metastases were located either in level II, III, or IV or in a combination of these 3 levels. Level V was involved in only 1 case (6%). Conclusion: It is well justified to perform a salvage SND (levels II, III, and IV) for pharyngeal and laryngeal carcinoma after primary radiation. In carefully selected cases of supraglottic and oropharyngeal carcinoma, a superselective ND also appears as an efficient option.